2017
DOI: 10.1017/s095026881700190x
|View full text |Cite
|
Sign up to set email alerts
|

Fine-temporal forecasting of outbreak probability and severity: Ross River virus in Western Australia

Abstract: Health warnings of mosquito-borne disease risk require forecasts that are accurate at fine-temporal resolutions (weekly scales); however, most forecasting is coarse (monthly). We use environmental and Ross River virus (RRV) surveillance to predict weekly outbreak probabilities and incidence spanning tropical, semi-arid, and Mediterranean regions of Western Australia (1991-2014). Hurdle and linear models were used to predict outbreak probabilities and incidence respectively, using time-lagged environmental vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 45 publications
1
42
1
Order By: Relevance
“…The model correctly predicts that RRV disease is year-round endemic in tropical, northern Australia with little seasonal variation due to temperature, and seasonally epidemic in temperate, southern Australia. These results provide a mechanistic explanation for idiosyncrasies in RRV temperature responses observed in previous studies ( Hu et al, 2004 ; Gatton et al, 2005 ; Bi et al, 2009 ; Werner et al, 2012 ; Koolhof et al, 2017 ). A population-weighted version of the model (assuming a two-month lag between temperature and human cases based on mosquito and disease development times) also accurately predicts the seasonality of human cases nationally.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…The model correctly predicts that RRV disease is year-round endemic in tropical, northern Australia with little seasonal variation due to temperature, and seasonally epidemic in temperate, southern Australia. These results provide a mechanistic explanation for idiosyncrasies in RRV temperature responses observed in previous studies ( Hu et al, 2004 ; Gatton et al, 2005 ; Bi et al, 2009 ; Werner et al, 2012 ; Koolhof et al, 2017 ). A population-weighted version of the model (assuming a two-month lag between temperature and human cases based on mosquito and disease development times) also accurately predicts the seasonality of human cases nationally.…”
Section: Introductionsupporting
confidence: 74%
“…Moreover, compared to vector-borne diseases in lower-income settings, RRV case diagnosis and reporting are more accurate and consistent, and variation in socioeconomic conditions (and therefore housing and vector control efforts) at regional and continental scales is relatively low. Previous work has shown that in some settings temperature predicts RRV cases ( Gatton et al, 2005 ; Bi et al, 2009 ; Werner et al, 2012 ; Koolhof et al, 2017 ), while in others it does not ( Hu et al, 2004 ; Gatton et al, 2005 ). Understanding RRV transmission ecology is critical because the virus is a candidate for emergence worldwide ( Flies et al, 2018 ), and has caused explosive epidemics where it has emerged in the past (infecting over 500,000 people in a 1979–80 epidemic in Fiji) ( Klapsing et al, 2005 ).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations